2020
DOI: 10.1089/thy.2019.0590
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences Around Extent of Surgery in Low-Risk Thyroid Cancer: A Discrete Choice Experiment

Abstract: Background: Patient preferences pertaining to surgical options for thyroid cancer management are not well studied. Our aim was to conduct a discrete choice experiment (DCE) to characterize participants' views on the relative importance of various risks and benefits associated with lobectomy versus total thyroidectomy for lowrisk thyroid cancer. Methods: Adult participants with low-risk thyroid cancer or a thyroid nodule requiring surgery were asked to choose between experimentally designed surgical options wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Surgery is still the firstline treatment for most low-risk PTMCs. However, postoperative complications, including permanent recurrent laryngeal nerve paralysis, hypoparathyroidism, osteoporosis, and cardiac events, decrease patients' quality of life [32][33][34]. According to some studies, surgery can be considered as an overtreatment clinical strategy for such a low-risk but high-incidence disease [35].…”
Section: Discussionmentioning
confidence: 99%
“…Surgery is still the firstline treatment for most low-risk PTMCs. However, postoperative complications, including permanent recurrent laryngeal nerve paralysis, hypoparathyroidism, osteoporosis, and cardiac events, decrease patients' quality of life [32][33][34]. According to some studies, surgery can be considered as an overtreatment clinical strategy for such a low-risk but high-incidence disease [35].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that some of these “recurrences” are in fact, persistent disease, particularly when “new” lymph nodes are seen in lateral neck shortly after initial thyroidectomy, and that many could have been avoided with detailed lymph node mapping preoperatively. Ahmadi et al 11 evaluated patient preferences regarding initial lobectomy vs. total thyroidectomy. The risk for recurrence was the most important factor in decision-making, followed by the potential need for CT.…”
Section: Discussionmentioning
confidence: 99%
“…HRQoL was 1.5-times worse in patients having undergone total thyroidectomy (95% CI, 1.04-2.12) and 2.3-times worse in those having undergone total thyroidectomy and neck dissection (95% CI, 1.10-4.80) compared with patients having undergone lobectomy [29]. Finally, a recent online survey asking 150 patients to state their choice between total thyroidectomy and thyroid lobectomy found that their choices were, on average, determined for 35% of patients by the risk of cancer recurrence, 28% by the need for a second operation, 19% by the risk of recurrent nerve damage, and 9% by the risk of hypocalcemia and need for thyroid hormone treatment [30]. Oncologic considerations thus seem to be more important to patients than complications, and we will focus on this aspect of thyroid lobectomy in the following paragraphs.…”
Section: Why Thyroid Lobectomy?mentioning
confidence: 99%
“…Even if preoperative patient selection is very careful and careful intraoperative evaluation excludes patients with suspected extrathyroidal extension or lymph node metastases, at least 30% of patients may still require completion thyroidectomy secondarily due to higher-risk features that can only be ascertained upon definitive histopathological and molecular analysis of the tumor [56,57]. Patient preference, recently studied via an online questionnaire, found that among other considerations, patients favored lobectomy over total thyroidectomy as long as the risk of needing a completion operation was below 30% [30]. Unfortunately, patient preferences do not fall within the estimated 34-59% rate of completion thyroidectomy, as cited above.…”
Section: Oncologic Considerations: Completion Thyroidectomy and Survivalmentioning
confidence: 99%